2022
DOI: 10.3917/all.239.0194
|View full text |Cite
|
Sign up to set email alerts
|

Savoir controversé et polarisation sociale. Une étude du débat politique allemand sur le climat de 2017 à 2021

Abstract: Il existe aujourd’hui un large consensus quant à l’importance du savoir dans la mise au point d’une politique climatique efficace, et les appels pour une amélioration des relations entre la science et la politique ne cessent de se multiplier. Dans le même temps, il y a non seulement controverse sur la définition d’un savoir pertinent pour la politique climatique, sur la question des disciplines scientifiques destinées à jouer un rôle à cet égard et sur la manière dont diverses connaissances sont rendues dispon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As a boundary activity, efforts to increase the impact of research on policy not only need to communicate research findings to policymakers, but also enable policymakers to access, engage with and see the relevance of research. However, studies have shown that some types of research are easier to communicate than others and have more resources for boundary spanning activities, leading to findings from some disciplines and in some policy areas being more often and more effectively translated than in other disciplines and areas (Bartl 2022 ; Victor 2015 ; Zeigermann 2022 ). The translation process can therefore not be seen as neutral, but as a strategic activity of interpreting and producing information (Hassenteufel and Zeigermann 2021 ) that may have an impact on the understanding of, and development of solutions to, wicked problems.…”
Section: The Mechanisms Of Boundary Spanning Activitiesmentioning
confidence: 99%
“…As a boundary activity, efforts to increase the impact of research on policy not only need to communicate research findings to policymakers, but also enable policymakers to access, engage with and see the relevance of research. However, studies have shown that some types of research are easier to communicate than others and have more resources for boundary spanning activities, leading to findings from some disciplines and in some policy areas being more often and more effectively translated than in other disciplines and areas (Bartl 2022 ; Victor 2015 ; Zeigermann 2022 ). The translation process can therefore not be seen as neutral, but as a strategic activity of interpreting and producing information (Hassenteufel and Zeigermann 2021 ) that may have an impact on the understanding of, and development of solutions to, wicked problems.…”
Section: The Mechanisms Of Boundary Spanning Activitiesmentioning
confidence: 99%